RELEVANSI KONSEP KELUARGA SEBAGAI PENDIDIK PERTAMA DALAM FILSAFAT PENDIDIKAN ISLAM DI ERA MODERN - Azaliya Putri Azizah; Melisa Nur Alvilayli; , Nafisah R.A; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
The family occupies a strategic position as the first educational institution in the process of shaping a child's personality. However, the rapid development of technology, changes in parenting patterns, and the increasing influence of external environments have weakened the educational function of the family, leading to challenges in the formation of children's moral and spiritual values. This study aims to analyze the role of the family as the first educational institution from the perspective of Islamic philosophy. The research employs a qualitative approach using a library research method. Data were collected from the Qur'an, Hadith, books on Islamic educational philosophy, and relevant scientific journal articles. The data were analyzed through content analysis by identifying key concepts, categorizing themes, and interpreting their philosophical meanings. The findings reveal that, in Islamic philosophy, the family is not merely a biological and social unit but also the primary educational institution responsible for nurturing faith, morality, and character. The family serves as the first environment for preserving and developing the child's innate nature (fitrah) through faith-based education, moral guidance, exemplary behavior, and habituation of worship. In the modern era, strengthening the educational role of the family has become increasingly urgent to address moral challenges arising from globalization and digital transformation. Therefore, the family remains the fundamental foundation for achieving the objectives of Islamic education and developing morally upright individuals.